1999
DOI: 10.1103/physrevb.60.r6953
|View full text |Cite
|
Sign up to set email alerts
|

Middle-field cusp singularities in the magnetization process of one-dimensional quantum antiferromagnets

Abstract: We study the zero-temperature magnetization process (M −H curve) of one-dimensional quantum antiferromagnets using a variant of the density-matrix renormalization group method. For both the S = 1/2 zig-zag spin ladder and the S = 1 bilinear-biquadratic chain, we find clear cusp-type singularities in the middle-field region of the M − H curve. These singularities are successfully explained in terms of the double-minimum shape of the energy dispersion of the low-lying excitations. For the S = 1/2 zig-zag spin la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
92
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(97 citation statements)
references
References 53 publications
4
92
0
1
Order By: Relevance
“…However, in the bosonization theory the dimerization operator is proportional to cos( √ 8πφ − + πM ), whose average vanishes because of Eq. (24). We thus conclude that the nematic phase does not have a spontaneous dimerization.…”
Section: A Bosonization Theory Revisitedmentioning
confidence: 64%
See 1 more Smart Citation
“…However, in the bosonization theory the dimerization operator is proportional to cos( √ 8πφ − + πM ), whose average vanishes because of Eq. (24). We thus conclude that the nematic phase does not have a spontaneous dimerization.…”
Section: A Bosonization Theory Revisitedmentioning
confidence: 64%
“…It has been established that in zero magnetic field the ground state of the antiferromagnetic J 1 -J 2 spin chain undergoes a phase transition from a critical phase with gapless excitations for J 2 < J 2c = 0.2411J 1 to a gapped phase with spontaneous dimerization for J 2 > J 2c as J 2 increases. 17,18,19,20,21,22,23 It has also been revealed that the model exhibits cusp singularities and a 1/3-plateau in the magnetization curve 24,25 as well as a vector chiral order in the case of anisotropic exchange couplings 26,27,28 or under magnetic field. 29,30,31,32 In this paper we concentrate on the ferromagnetic case (J 1 < 0) of the J 1 -J 2 spin chain (1) in magnetic field which partially polarizes spins to the +z direction.…”
Section: Introductionmentioning
confidence: 99%
“…In such a state, the system approximately decouples into a gapped antisymmetric sector and a gapless symmetric sector, the latter being described by the Tomonaga-Luttinger liquid ͑TLL͒. An alternative two-component TLL scenario [11][12][13] assumes the existence of the Tomonaga-Luttinger liquid in both sectors and implies the absence of the chiral order.…”
Section: Introductionmentioning
confidence: 99%
“…[16] In addition, this singularity has also been reported for other quantum spin systems: the zigzag spin chain and the frustrated Kondo necklace. [17][18][19][20] …”
Section: Introductionmentioning
confidence: 99%